In vitro and in vivo bacterial antifouling properties of phosphite plasma-treated silicone. Issue 2 (7th January 2019) - Akdogan, Ebru; Demirbilek, Murat; Sen, Yasin; Onur, Mehmet Ali; Azap, Ozlem Kurt; Sonmez, Erkin; Sirin, Hasret Tolga; Mutlu, Mehmet
Abstract : In order to improve their bacterial antifouling property, silicone surfaces were functionalized through the plasma polymerization (PP) technique using diethyl phosphite as the precursor. The functionalized surfaces were characterized using contact angle measurements, contact angle titration, Fourier transform infrared–attenuated total reflection spectroscopy and in vitro cytotoxicity assay. The amount of non-specific protein adsorption and the conformational changes of surface-adsorbed proteins were investigated. Antifouling properties of the surfaces were evaluated in vitro and in vivo. PP functionalization generated a hydrophilic and amphoteric surface with a very good protein and bacterial antifouling property and caused less conformational changes on the secondary structure of surface-adsorbed proteins. In in vivo conditions, no slime layer was formed around bacteria that adhered on the PP-functionalized surface. It is concluded that the amphoteric nature of the PP-functionalized surface is the reason for the good antifouling property.